Hands-On Functional Programming in Rust : Build modular and reactive applications with functional programming techniques in Rust 2018. - Johnson, Andrew (Packt Publishing, 2018)
Functional programming allows developers to divide programs into smaller, reusable components that ease the creation and maintenance of software as a whole. Combining power of Rust, you can develop robust applications that fulfill modern day software requirements. This book will help you discover Rust features to build software in a functional way.